The Tree That Leads to Death: Yew Fruit: Yew Fruit - Özesen, Toygün Anıl; Kaya, Kenan; Malkoç, Mehmet Ali; Gülmen, Mete Korkut (The Bulletin of Legal Medicine, 2022)
Yew fruit can cause a large number of human and animal poisoning and can be highly toxic. This is achieved by the taxon alkaloids (Taxin A and Taxin B) that cause cardiotoxic effects in its structure. Taxins cause cardiac dysrhythmia with the effect of calcium channel antagonism in cardiac myocytes and cause a clinical deterioration leading to death. The diagnosis of yew fruit poisoning is usually made by identifying plant parts in the digestive system. With the recent technological developments and the development of toxicological diagnosis methods, the diagnosis of metabolites in lower doses has begun to be made more easily with clinical suspicion.